Governance, Corruption, and Economic Performance - Gupta, Sanjeev; Abed, George (Washington, D.C. : International Monetary Fund, 2002)
This volume presents 18 IMF research studies on the causes and consequences of corruption, as well as how it can most effectively be combated to improve governance, increase economic growth, and reduce poverty. The authors examine how civil service wages affect corruption, the impact of natural resource availability on corruption, the impact of corruption on a country's income distribution and incidence of poverty, and the effect of corruption on government expenditures on health and education.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet